Analisis Penggunaan TikTok terhadap Pola Pencarian Informasi Digital pada Mahasiswa Sekolah Vokasi - Fatih Syahira Nugrainti; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The evolution of digital technology has transformed how university students access information; the internet has become a dynamic visual ecosystem with penetration projected to reach 80% by 2025. This phenomenon has driven the transformation of social media platforms like TikTok into primary search engines for Generation Z, a demographic that prioritizes instant gratification and visual formats. This study aims to analyze the shift in digital information-seeking patterns among students at the IPB Vocational School regarding TikTok, as well as to explore the information verification strategies they employ. A descriptive qualitative approach was utilized, with data collected through in-depth interviews, participant observation, and document analysis involving active IPB Vocational School students. Drawing on Niche Theory, the results indicate that TikTok has established dominance over conventional search engines in the category of technical tutorial searches, primarily due to its efficiency and speed. Scientific findings suggest that short-video formats satisfy cognitive needs through media richness (audio-visual content), which helps reduce ambiguity when understanding precise practical procedures. Furthermore, the "For Your Page" (FYP) feature shifts behavior from active searching to the passive reception of information automatically curated by algorithms. Regarding validity, students employ "social proof" mechanisms via comment sections and practice source triangulation cross-checking information against Google or scholarly articles to avoid misinformation. The study concludes that while TikTok has evolved into a crucial information-seeking tool for vocational students, strong digital literacy awareness remains essential to ensure the accuracy of the information consumed and to effectively support the development of their practical competencies.